2020
DOI: 10.13181/mji.oa.204390
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of respiratory infection due to air pollution during natural disasters

Abstract: BACKGROUND Wildfire and volcano eruption occurred in Indonesia due to its geographical location, climate change, global warming, and human behavior. Various substances produced an increased risk of experiencing health problems, including respiratory infection. Evidence about the effect of pulmonary infection during natural disasters is still limited. This study was aimed to review and elaborate on previous studies to determine the effect of air pollution exposure during natural disasters and respiratory infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…A systematic review of air pollution exposure during natural disasters including wildland fires and volcanic eruptions concluded that PM generated by these events was associated with increased rates of acute respiratory infection, pneumonia, bronchitis, and bronchiolitis. 30 A consistent association across multiple studies was observed between exposure to wildfire-related particulate matter less than 2.5 µm in diameter (PM 2.5 ) and increased ED visits and hospitalizations for acute respiratory infection. 31 , 42–47 Delfino et al found that during wildfires in Southern California, the number of hospital admissions for pneumonia increased by 1.3x (95% CI 1.17, 1.48) and admissions for acute bronchitis/bronchiolitis increased by 1.6x (95% CI 1.09, 2.29) among area residents.…”
Section: Climate Change and Respiratory Viral Infectionmentioning
confidence: 81%
See 1 more Smart Citation
“…A systematic review of air pollution exposure during natural disasters including wildland fires and volcanic eruptions concluded that PM generated by these events was associated with increased rates of acute respiratory infection, pneumonia, bronchitis, and bronchiolitis. 30 A consistent association across multiple studies was observed between exposure to wildfire-related particulate matter less than 2.5 µm in diameter (PM 2.5 ) and increased ED visits and hospitalizations for acute respiratory infection. 31 , 42–47 Delfino et al found that during wildfires in Southern California, the number of hospital admissions for pneumonia increased by 1.3x (95% CI 1.17, 1.48) and admissions for acute bronchitis/bronchiolitis increased by 1.6x (95% CI 1.09, 2.29) among area residents.…”
Section: Climate Change and Respiratory Viral Infectionmentioning
confidence: 81%
“… 17 Convincing epidemiologic data has linked air pollution exposure with increased incidence of viral respiratory infections like upper respiratory tract (URI) infections, 18 , 19 bronchitis, 20 and lower respiratory tract infections (LTRI) 21 , 22 such as pneumonia 23 , 24 and bronchiolitis. 25 , 26 Similarly, temperature, 27 , 28 humidity, 29 and extreme weather events 30–32 have also been directly and indirectly associated with respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…Human diseases are often given names by stakeholders outside of the medical sphere. As a counterexample, Pneumonoultramicroscopicsilicovolcanoconiosis , referred to as pneumoconiosis or silicosis, was coined by Everett M. Smith in 1935 [65,66]. Literally, the 45-letter neologism is “a form of a chronic lung disease caused by the inhalation of fine silicate or quartz dust”, according to the Oxford English Dictionary Online (OED Online).…”
Section: Resultsmentioning
confidence: 99%